2016
DOI: 10.1016/j.pnpbp.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

MAO and aggression

Abstract: observations of epigenetic regulation of MAO activity. MAO inhibition raises brain amine levels, a fact exploited for antidepressant effect, and now being incorporated into multi-target compounds to combat neurodegenerative conditions. Catalysis, mechanism and inhibition of MAO, important both for measuring levels in tissues and for drug design, are described. Of the successful irreversible drugs that inhibit MAO B, the classic non-selective MAO inhibitor, phenelzine, the MAO B-selective inhibitor deprenyl (se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Both human [28] and animal [29] studies confirmed the important role of MAO in aggressive behavior, assumed to be achieved by modulating corticolimbic circuits affecting social information processing and emotional responsiveness. Platelet MAO-B activity was reported to be reduced in different psychopathological and disinhibited, criminal, and violent behaviors and aggression [21,[30][31][32][33].…”
Section: Introductionmentioning
confidence: 67%
“…Both human [28] and animal [29] studies confirmed the important role of MAO in aggressive behavior, assumed to be achieved by modulating corticolimbic circuits affecting social information processing and emotional responsiveness. Platelet MAO-B activity was reported to be reduced in different psychopathological and disinhibited, criminal, and violent behaviors and aggression [21,[30][31][32][33].…”
Section: Introductionmentioning
confidence: 67%